Analysis of Students Scientific Literacy in Integrated Acid-Base Learning Socioscientific Issues - Haryanto, Robby; Rahmawati, Yuli; Saputra, Irwan (Universitas Pendidikan Mandalika, 2025)
This study aims to obtain the profile of students' scientific literacy in acid-base learning through the integration of socioscientific issues. The study was conducted on grade 11 students of SMA Negeri 33 Jakarta. The research methodology used was qualitative. Research data were obtained through observation, reflection journals, science literacy tests, student worksheets, and interviews. The socioscientific issues approach begins with introducing acid-base issues, introducing concepts, playing roles, and learning reflections. The results of the study showed that students can develop their ability to express opinions and foster concern for environmental conditions. The profile of students' scientific literacy is quite good in terms of knowledge and competence. In terms of context, most students are at the scientific illiteracy and nominal scientific literacy levels. Based on the results of the science literacy test, the majority of students are at the scientific illiteracy and nominal scientific literacy levels.